Low-Temperature Extraction of Lipid Fractions from Vegetable Raw Materials Using Liquefied Freons - Osetskyi, Oleksandr; Sevastianov, Stanislav; Yevlash, Victoria; Potapov, Volodymyr; Piliugina, Iryna; Bilyi , Dmytro (Problems of Cryobiology and Cryomedicine, 2023)
This paper presents the method of cryogenic extraction by means of liquefied freons. Using the equipment to extract lipid fractions from biological raw materials, a freon extract from bay leaves (Laurus nobilis) was experimentally obtained. A low-temperature extraction of lipid fractions from bay leaves was first realized using liquefied freons within the temperature range of –2...–8°С. The difference in composition of these fractions from that of the oils, obtained within the standard temperature ranges of 30...50°С was shown. Dependence of the finished product weight on extraction time as a result of three consecutive cycles of 23 hrs each was demonstrated. Using gas chromatography, 68 components of freon extract were identified, and their quantitative composition and dominant compounds were detected. The content of essential oils and aroma-forming substances, stipulating the number of odour units was specified. These findings may be the basis for novel technological approaches to separation of lipid fractions, isolated from biological raw materials of plant and animal origin. Here, we described the device version with a three-stage cryogenic system of freon solvent recovery for effective implementation of the designed technology. Probl Cryobiol Cryomed 2023; 33(1): 038–049